Advancing Diversity, Equity, and Inclusion: Operationalizing the Inclusive Professional Framework to Develop STEM Faculty Change Agents - Selyna Pérez Beverly; Quintana M. Clark; Lucas B. Hill; Donald L. Gillian-Daniel (Education Sciences)
With the need for diverse representation in STEM, institutions have found ways to improve Diversity, Equity, and Inclusion (DEI) through programs and broad institutional policies. Yet, improving the awareness of faculty regarding DEI can be instrumental in improving conditions for underrepresented students in STEM. This article discusses the Inclusive Professional Framework (IPF) and its operationalization through a summer professional development program, the Aspire Summer Institute (ASI). Findings from longitudinal survey data indicated that participants increased their knowledge of, and confidence in, DEI practices. Qualitative data revealed that participants gained a personal awareness of the impact that identity had on their professional responsibilities. As a result, participants adapted their teaching approaches and changed how they interacted with students and colleagues, as well as how they contributed to institutional efforts around DEI in STEM.